PENGARUH SENAM SEHAT ANAK INDONESIATERHADAP KEBUGARAN JASMANI SISWA KELAS V SDN 131/II SKB KABUPATEN BUNGO PROVINSI JAMBI - Deddy Rahmat Saputra; Desi Tri Susanti (PRODI PJKR UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2023)
Abstract Gymnastics is a sport that is carried out en masse, starting from the elementary, middle, upper and public levels. In the past, gymnastics was very cultured, this is evidenced by the absence of differences in almost all circles of the gymnastics community both in groups and collectively, old, young, male, and female exercising together. This study aims to determine